Dissemination and Implementation of Evidence‐Based Dementia Care Using Embedded Pragmatic Trials. (26th June 2020) - Gitlin, Laura N.; Baier, Rosa R.; Jutkowitz, Eric; Baker, Zachary G.; Gustavson, Allison M.; Sefcik, Justine S.; Hodgson, Nancy A.; Koeuth, Sokha; Gaugler, Joseph E.
Abstract : There are many nonpharmacologic interventions tested in randomized clinical trials that demonstrate significant benefits for people living with Alzheimer's disease (AD) and AD‐related dementia, their care partners, or professional care providers. Nevertheless, with few exceptions, proven interventions have not been translated for delivery in real‐world settings, such as home care, primary care, hospitals, community‐based services, adult day services, assisted living, nursing homes, or other healthcare systems (HCSs). Using embedded pragmatic clinical trial (ePCT) methods is one approach that can facilitate dissemination and implementation (D&I) of dementia care interventions. The science of D&I can inform the integration of evidence‐based dementia care in HCSs by offering theoretical frameworks that capture field complexities and guiding evaluation of implementation processes. Also, D&I science can suggest evidence‐based strategies for implementing dementia care in HCSs. Although D&I considerations can inform each stage of dementia care intervention development, it is particularly critical when designing ePCTs. This article examines fundamental considerations for implementing dementia‐specific interventions in HCSs and how best to prepare for successful dissemination upstream in the context of ePCTs, thereby illustrating the critical role of the D&I Core of the National Institute on Aging Imbedded Pragmatic Alzheimer's Disease and AD‐Related Dementias Clinical Trials Collaboratory. The scientific premise of the D&I Core is that having the "end" in mind, upfront in the design and testing of dementia care programs, can lead to decision‐making that optimizes the ultimate goal of wide‐scale D&I of evidence‐based dementia care programs in HCSs. J Am Geriatr Soc 68:S28–S36, 2020 .